Application of Coconut Shell Biochar and Rhizobacteria Consortium to Increase Cocoa Production (Theobroma cacao L.) - Laurenze, Reynaldi; Ala, Ambo; Saleh, Ifayanti Ridwan (Indonesian Coffee and Cocoa Research Institute, 2023)
The decline in Indonesia’s cocoa production as a result of soil fertility degra dation causes fertilization to become one of effective effects. Because of that, it is possible to restore soil fertility potential by using soil fertility enhancer biochar combined with rhizobacteria consortium to create suitable conditions for plant.This research was aimed to study and investigate coconut shell biochar interacts with rhizobacteria in increasing cocoa production. This research was conducted at Kodeoha, North Kolaka, Southeast Sulawesi from September 2022 until March 2023. A split plot design with three replications each consisted of two experimental units was used as an experimental design. Biochar dosage as the main plot consisted of four levels, namely 0 ton ha-1 (control), 2.5 ton ha-1, 5 ton ha-1, and 7.5 ton ha-1 and rhizobacteria concentration as the sub plots consisted offour levels, namely 0 mL L-1, 50 mL L-1, 100 mL L-1, and 150 mL L-1. Results of this research showed a significant interaction between biochar 5 tons ha-1 and rhizobacteria 100 mL L-1 which provide best result for chlorophyll a (336 μmol m-2), chlorophyll b (150 μmol m-2), and total chlorophyll (484 μmol m-2). The interaction between biochar 5 tons ha-1 and rhizobacteria 150 mL L-1 showed the best results for number of harvested pods per tree (10.00 pods), bean weight per tree (606 g trees-1), stomata opening area (31 μm2). The interaction between biochar 7.5 tons ha-1 and rhizobacteria 150 mL L-1 showed the best results on the weight of 100 dry beans at water content 8% (159.03 g)